Molecular basis of hypoxia tolerance in the whale brain - Krüger, Alena (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2019)
Marine mammals are routinely exposed to low oxygen conditions when submerged. While physiological adaptations that reduce oxygen consumption and improve oxygen storage are well studied, the molecular mechanisms of the cerebral hypoxia tolerance in diving mammals are still widely unknown. Enhanced anaerobic energy production and general energy saving mechanisms via hypometabolism could help the diving brain to survive hypoxic periods. The aim of this work was to reveal basic molecular differences in the brain of whales and their closest terrestrial relative, the cattle. By using transcriptome analysis, gene expression differences were examined, and based on these results further molecular adaptations to diving were investigated. Transcriptomes of the visual cortex of the killer whale (Orcinus orca), the longfinned pilot whale (Globicephala melas), as well as the cerebellum of the long-finned pilot whale and the visual cortex of the cow (Bos taurus) were sequenced. In order to increase the number of replicates, additional brain transcriptomes of cattle brain, as well as minke whale (Balaenoptera acutorostrata) brain and bowhead whale (Balaena mysticetus) brain from the NCBI public SRA database were included in the analyses. Comparison of the brain transcriptomes of whales and cattle revealed an increased aerobic capacity in the whale brain(Chapter I). This was suggested based on a significantly higher expression of an above-average number of transcripts involved in oxidative phosphorylation and the electron transport chain in the whale brain. In contrast to seals, whales seem to have developed a more efficient use of oxygen to sustain brain activity instead of a reduced metabolism to save energy. Additionally, the high aerobic capacity might represent an adaptation for the rapid regeneration of ATP production immediately after resurfacing. However, enhanced aerobic metabolism also increases the formation of toxic reactive oxygen species (ROS). Significantly higher expression levels of transcripts involved in the ...